First Full Vector Archeomagnetic Data From Northern Mexico. (28th September 2021) - Tchibinda Madingou, B.; Perrin, M.; Hervé, G.; Hernàndez Cardona, A.; Alva‐Valdivia, L. M.; Cruz Antillón, R.
Abstract: Several regional secular variation curves of the geomagnetic field have been proposed for Mexico over the last millennia. Despite a fairly large number of archeomagnetic data, these curves remain imprecise because of an uneven quality and geographic distribution, with a lack of data in Northern Mexico. Nine pottery kilns were sampled in Casas de Fuego, an archeological site in the Chihuahua state. These kilns belong to the Casas Grandes culture and were in use between 1250 and 1450 CE. Rock magnetic experiments indicate that the main magnetic phase is a Ti‐poor titanomagnetite in the SD range. Mean characteristic directions per kiln were estimated by alternating field and/or thermal demagnetization, and archeointensities with the Thellier‐Thellier protocol, after correction for anisotropy and cooling effects. The nine directions and eight intensities agree with data from USA and Mexico but do not support the peak in inclination modeled by the Mexican secular variation curve around 1200–1300 CE. For the last millennium, the Western North American curve is consistent with the SHAWQ2k global model, and better reflects the secular variation in Northern Mexico. For intensity, neither the SHAWQ2k model nor the regional intensity curve can depict the rapid secular variation that likely occurs circa 1500 CE. The Casas de Fuego results are the first full vector determinations obtained in Northern Mexico. Plain Language Summary: Archeological baked clays are the best material to reconstitute the past secular variation of the geomagnetic field because they acquired a generally stable thermoremanent magnetization parallel and proportional to the field at the time of their baking. Archeomagnetic data are used to build regional curves and global models of the secular variation. Several curves have been proposed for Mexico over the past few years, but they remain imprecise because of an uneven quality and geographic distribution of data. Data are especially lacking in Northern Mexico and for this reason, we studied nine pottery kilns from Casas de Fuego, an archeological site in Chihuahua state. These kilns belong to the Casas Grandes culture and were in use between 1250 and 1450 CE. The nine new directions and eight new intensities constitute the first full vector determinations obtained in Northern Mexico. For direction, our new data agree with the Western North American secular variation curve but not with the Mexican curve. Casas de Fuego and other regional data show a rapid secular variation circa 1500 CE that is not depicted by current regional and global geomagnetic models for the intensity curve. Key Points: Archeomagnetic study at Casas de Fuego archeological site, Chihuahua state Directional and intensity results from nine kilns, in use between 1250 and 1450 CE First full vector determinations of the geomagnetic field in Northern Mexico